Emerging technologies for health and medicine : virtual reality, augmented reality, artificial intelligence, Internet of Things, robotics, Industry 4.0 /: virtual reality, augmented reality, artificial intelligence, Internet of Things, robotics, Industry 4.0. (2018) - Unknown
No abstract available